2007
DOI: 10.18388/abp.2007_3240
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effect of photodynamic therapy against methicillin-resistant Staphylococcus aureus strain with the use of various porphyrin photosensitizers.

Abstract: Photodynamic therapy (PDT) is based on photosensitizers activated by light of appropriate wavelength. Their activation leads to generation of singlet oxygen and free radicals responsible for the cytotoxic effect. The aim of this project was to compare the bactericidal effect of PDT using different porphyrin photosensitizers against a methicillin-resistant Staphylococcus aureus strain. Exogenous sensitizers (protoporphyrin IX and newly synthesized derivative, protoporphyrin diarginate) induced a 3 log10-unit re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Other studies that tested the combination of antibiotics and PDT used the disk diffusion method to detect synergistic combinations . In these experiments, S. aureus cultures were treated with PDT and subcultured on TSA medium.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that tested the combination of antibiotics and PDT used the disk diffusion method to detect synergistic combinations . In these experiments, S. aureus cultures were treated with PDT and subcultured on TSA medium.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now mainly preliminary investigations have been performed, such as analyzing the survival rate of bacteria in vitro, depending on the type and dose of the photosensitizer, wavelength and illumination duration (Maisch et al, 2005;Grinholc et al, 2007a;Sharma et al, 2008;Peloi et al, 2008).…”
Section: F Photodynamic Therapymentioning
confidence: 99%
“…From a clinical point of view, an important issue is easy killing of the multi-resistant MRSA strains in response to photodynamic therapy as development of resistance to this therapy seems to be unlikely, in contrast to the quick gaining of resistance towards different antibiotics and other antibacterial agents (Hamblin & Hasan, 2004;Grinholc et al, 2007a). Grinholc et al (2008b) reported that the response to photodynamic inactivation with protoporphyrin diarginate (PPArg 2 ) was different among various clinical MSSA and MRSA strains and ranged from 0 to 3 log 10 unit reduction in viable counts.…”
Section: F Photodynamic Therapymentioning
confidence: 99%
“…In Poland the group of Prof. Graczyk sensitized a new class of protoporphyrin IX amino acid derivatives which as a result of the attachment of two arginines became well soluble in aquatic solutions and possesses amphiphilic character (11,12). Our laboratory has recently demonstrated high effectiveness of porphyrin‐based photoinactivation against methicillin‐resistant S. aureus strains (MRSA; 13), without significant impact on healthy human dermal fibroblasts but having high therapeutic potential in case of human cervical carcinoma and colon carcinoma cells in vitro (14–16). Moreover, we have previously reported that the bactericidal effect of PDT based on protoporphyrin diarginate (PPArg 2 ) sensitizer of S. aureus could be strain‐dependent as effectiveness of PDT ranged from 0 to 3.6 log 10 unit reduction in viable counts (17).…”
Section: Introductionmentioning
confidence: 99%
“…S1), delivered by the Institute of Optoelectronics, Military University of Technology (Warsaw, Poland) was used as a sensitizer. PPArg 2 was dissolved in distilled water to give a 10 m m stock solution, filtered‐sterilized and stored at a −20°C in darkness until use (13,16,17).…”
mentioning
confidence: 99%